Gaya Komunikasi Dosen dalam Proses Pembelajaran di Prodi Komunikasi Universitas Sari Mutiara - Nurhawati Simamora; Rachel Mia L. Lbn. Toruan; Mega Ulva Sari Sihombing; Novira Sazelika (Universitas Sari Mutiara Indonesia, 2023)
This study aims to analyze communication styles in overcoming learning boredom in the Communication course. The study emphasizes a qualitative approach, involving 2 lecturers, one lecturer as an observer and one lecturer acting as a direct participant, while the number of students is 45 people in class A. The results of the study indicate that in overcoming learning boredom, lecturers develop an active communication style, but still prioritize assertiveness, take full social initiative so that students can imitate, are able to integrate with their social environment, are able to express their opinions emotionally but in a controlled manner, send information with full attention, give orders but show assertiveness, and attention. In addition, lecturers have an imperfect Emotive style communication style, an unstable Director style, a Reflective style, and have a careful supportive style. The lecturer's communication style in learning will have an impact on the actualization and implementation of his social life.